PENGARUH HERBAL COMPRESS BALL TERHADAP PENURUNAN NYERI OTOT PADA LANSIA DI UPT PELAYANAN SOSIAL LANJUT USIA BINJAI TAHUN 2018 - Pujiastuti, Maria; Baeha, Loice Noni Faery; Pane, Jagentar (Jurnal Ilmiah Keperawatan, 2018)
Muscle pain is an unpleasant emotional and sensory experience related to the risk of actual or potential damage. The result of direct survey at UPT Elderly Social Services Binjai 2018 shows most of the elderly got muscle pain. One of the non-pharmacological therapies to reduce the scale of muscle pain is the Herbal Compress Ball therapy that effect comes from heat conduction that can increase regional blood flowing to the pain area, analgesic effects derived from herbal ingredients and aromatherapy essential oils give a relaxing effect.This study aims to determine the effect of Herbal Compress Ball on the decrease of muscle pain in the elderly.The measuring tool used was the observation sheet with the scale of muscle pain used was Wong-Baker FACES Rating Scale, divided into no pain, mild pain, moderate pain, severe controlled pain, and severe uncontrollable pain. The design of this study was an experimental one-group pre-post test design. The sampling technique was purposive sampling with 15 respondents. Data analysis was done by using test of wilcoxon sign rank test, and p value = 0,000 (p <0,05). This study shows that there is Influence of Herbal Compress Ball Against Muscle Pain Reduction in Elderly At UPT Binjai Elderly Social Service. It is expected that the researcher can further complement this research by adding a control group and comparing the effectiveness of Herbal Compress Ball between the intervention group and the control group.